Tax administration improvement as a factor of effective tax system development (Journal of Economic Research & Business Administration, 2016)
The article shows the role and importance of tax administration in the creation of an efficient tax system.Substantiates the place of the tax administration of the tax system as one of the important tools of the tax system.In the context of global financial instability, the growing importance of tax policy has acquired controlling (boosting) function of taxes. The neces-sity and suggested ways on improving the tax administration in order to modernize the tax system of Kazakhstan. The author suggests the possibil-ity of reforming the tax administration.Improving tax administration is directed mainly at reducing the shad-ow economy, ensuring completeness and timeliness of tax payments to the state budget and taxpayers.
Keywords: effective tax system; tax policy; tax administration; tax control; risk management system